The impact of the coronavirus pandemic crisis on inflation and interest rate policy in Poland - Grabia, Tomasz (Wpływ kryzysu wywołanego pandemią koronawirusa na przebieg inflacji i politykę stopy procentowej w Polsce, 2022)
The aim of the article was to investigate the impact of the crisis caused by the coronavirus pandemic on the course of inflation and interest rate policy in Poland. The empirical analysis reveals that prices ceased to be procyclical during the pandemic, and thus the resulting economic crisis contributed to a drop in inflation just in the first months of the pandemic. The main factor behind the subsequent rise in inflation was the decline in aggregate supply brought about by the lockdown. That was also accompanied by other reflationary factors, including the increase in some taxes and administered prices, as well as expansionary fiscal and monetary policy. In the case of the latter, the measures taken by the NBP led to almost zero interest rates in Poland. Consequently, the instrument has ceased to be a basic tool for influencing the economy in the future, at least during the crisis, when those rates should be further reduced (the so-called zero lower bound).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 47-58
Keywords: pandemic; economic crisis; inflation; interest rate; pandemia; kryzys gospodarczy; inflacja; stopa procentowa